Exploring the Typology, Teachers’ Perceptions, and Challenges of EMI Implementation at a Private Primary School - Handayani, Saufika; Setyarini, Sri; Rinekso, Aji Budi (JET ADI BUANA, 2022)
The trend of implementing EMI is getting raised across countries including Indonesia. Yet, the majority of previous studies merely focused on exploring EMI practices in tertiary education rather than primary-secondary education. Thus, this study is intended to uncover the implementation of EMI in a private primary school by focusing on three main issues: typology, teachers’ perceptions, and challenges. Qualitative approach featured with semi open-ended questionnaire and semi structured interview were applied in this study. The results reported the kind of EMI implemented in the school. Also, teachers’ perceptions and challenges of implementing EMI, and pedagogical implication are discussed in this study.